2016
DOI: 10.1007/s00066-016-1041-5
|View full text |Cite|
|
Sign up to set email alerts
|

Hypofractionated radiotherapy for localized prostate cancer

Abstract: AimThis article gives an overview on the current status of hypofractionated radiotherapy in the treatment of prostate cancer with a special focus on the applicability in routine use.MethodsBased on a recently published systematic review the German Society of Radiation Oncology (DEGRO) expert panel added additional information that has become available since then and assessed the validity of the information on outcome parameters especially with respect to long-term toxicity and long-term disease control.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 62 publications
0
29
1
Order By: Relevance
“…Our results indicate low sensitivity of prostate cancer to fractionation with high doses per fraction, much lower than that indicated by the small α/β mentioned above. This has been claimed by other authors, highlighting that the design of hypofractionated schemes for prostate cancer radiotherapy need to be proceed with caution [8].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our results indicate low sensitivity of prostate cancer to fractionation with high doses per fraction, much lower than that indicated by the small α/β mentioned above. This has been claimed by other authors, highlighting that the design of hypofractionated schemes for prostate cancer radiotherapy need to be proceed with caution [8].…”
Section: Discussionmentioning
confidence: 80%
“…This sensitivity appears in a low value of the α/β parameter of the linear-quadratic (LQ) model, where to calculate the equivalence between different fractionation schemes used in clinical practice, a value of α/β between 1.5 and 3.0 Gy is usually considered [6]. All of this has led to the proliferation of clinical studies and applications of hypofractionation in HDR-BT for prostate cancer, as in case of EBRT [7,8].…”
Section: Purposementioning
confidence: 99%
“…NHS England will audit RT practice and expect 70% of patients treated with EBRT to receive HFRT. The German Society of Radiation Oncology commissioned an expert review of hypofractionation [16] which concluded that hypofractionation was appropriate provided strict quality control using IMRT/IGRT was employed as in U.K. guidance. These recommendations are endorsed by the European Association of Urology Guidelines 2017 Edition [17].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Hypofractionation regimen employs a large dose per fraction of 2.2 to 4.0Gy daily, with a shorter overall treatment period which is usually less than 4 weeks [36]. In this study, 62% of patients were treated with various hypofractionation regimens; the most common regimen being 45Gy in 18 fractions over 3.5 weeks.…”
Section: Discussionmentioning
confidence: 88%